2009
DOI: 10.1177/0363546508328595
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Loading of 3 Achilles Tendon Repairs Simulating Early Postoperative Forces

Abstract: Epitendinous cross-stitch weave augmentation of Achilles tendon repairs may better allow for early stretching and ambulation after Achilles tendon repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
95
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 30 publications
10
95
1
3
Order By: Relevance
“…Results demonstrated the reduced strength of Achillon repaired tendons and a susceptibility to early repair elongation compared with both augmented and nonaugmented Krackow repairs. 22 Simulated Achillon repairs consistently failed during the first loading stage (20-100 N), while nonaugmented and augmented Krackow repairs primarily failed during the second (20-190 N) and third (20-369 N) stages, respectively. In the present study, no percutaneous repairs failed during the first loading stage (20- 100 N).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Results demonstrated the reduced strength of Achillon repaired tendons and a susceptibility to early repair elongation compared with both augmented and nonaugmented Krackow repairs. 22 Simulated Achillon repairs consistently failed during the first loading stage (20-100 N), while nonaugmented and augmented Krackow repairs primarily failed during the second (20-190 N) and third (20-369 N) stages, respectively. In the present study, no percutaneous repairs failed during the first loading stage (20- 100 N).…”
Section: Discussionmentioning
confidence: 92%
“…Loads were selected to mimic a progressive, postoperative rehabilitation protocol and were based on previous literature describing load ranges experienced by the Achilles tendon during passive ankle flexion (20-100 N) and walking in a cam walker with (190 N) and without (369 N) a 1-inch heel lift. 1,7,22,29 Load and displacement were monitored and recorded continuously throughout testing and reported as means 6 SDs. Repair failure was defined either as a precipitous drop in measured load, resulting from complete failure at the suture-tendon interface, or repair elongation that exceeded the maximum actuator travel distance of the tensile testing machine (.5 cm).…”
Section: Specimen Preparation and Biomechanical Testingmentioning
confidence: 99%
“…4,22 Prior studies have used initial linear stiffness as a surrogate measure of gapping. 10 The initial linear stiffness (N/mm) estimates the force (N) required to create a gap of 1 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies show that adding epitendinous suture reinforcement may improve tensile strength, gap resistance, and apposition of frayed tendon ends. 22,27 Lee et al showed in a cadaveric model that Krackow repairs with an epitendinous cross-stitch weave tolerated more cycles before gapping than nonaugmented Krackow repairs (2208 vs 502 cycles) (P ¼ .024). 21 In the present study, it is possible that augmentation contributed to the greater initial linear stiffness seen after open repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation